(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
This folktale comes in many forms: Sometimes the judge is Nasruddin, sometimes a Hassidic rabbi, sometimes a tribal chief. But the truth is (if there is a “truth”) that the situation described originated with the mother of the renowned philosopher/educator, Paolo Freire.